Construct validity of cognitive intraindividual variability: A replication study. (20th December 2022) - Scott, Bonnie M.; Royall, Donald R.; O'Bryant, Sid E.; Hilsabeck, Robin C.
Abstract: Background: We previously found intraindividual variability (IIV) in performance between cognitive domains to predict subsequent declines in cognitive and functional status over a 5‐year period in the Texas Alzheimer's Research and Care Consortium (TARCC) Hispanic Longitudinal Cohort. However, we later examined the construct validity and predictive utility of this metric in a follow‐up study and found that IIV‐between domains was driven primarily by IIV‐within the executive function domain in the non‐Hispanic cohort and by IIV‐within the language domain in the Hispanic cohort. The present study aimed to replicate these findings in two independent samples: (1) FRONTIER, and (2) HABLE. Methods: Baseline data for cognitively normal participants in the TARCC (N = 651), HABLE (N = 1199), and FRONTIER (N = 197) studies were included for analysis in the present study. All participants ranged from 50–95 years of age with 0–22 years of education. Although cognitive measures varied across studies, mean composite and standard deviation z‐scores were calculated from similar tasks for an Attention/Processing Speed, Language, Delayed Verbal Memory, and Executive Functioning domain. Measures of functional independence also varied across studies. Results: Across studies, non‐Hispanic individuals were generally older with higher levels of education, fewer depressive symptoms, and higher cognitive and functional status. Only variability in the executive domain was found to consistently differ between Hispanic and non‐Hispanic individuals across studies and no consistent between‐group differences were observed in the relationship between cognitive IIV scores with each other and with clinical characteristics and measures of general cognitive and functional status. Conclusions: Findings suggest that the construct validity and predictive utility of cognitive IIV scores varies across studies differing in methodology and clinical characteristics.